Association between previous negative biopsies and lower rates of progression during active surveillance for prostate cancer - Piccinelli, Mattia Luca; Luzzago, Stefano; Marvaso, Giulia; Laukhtina, Ekaterina; Miura, Noriyoshi; Schuettfort, Victor M; Mori, Keiichiro; Colombo, Alberto; Ferro, Matteo; Mistretta, Francesco A; Fusco, Nicola; Petralia, Giuseppe; et al. (World journal of urology, 2022)
PURPOSE: To test any-cause discontinuation and ISUP GG upgrading rates during Active Surveillance (AS) in patients that underwent previous negative biopsies (PNBs) before prostate cancer (PCa) diagnosis vs. biopsy naive patients. METHODS: Retrospective analysis of 961 AS patients (2008-2020). Three definitions of PNBs were used: (1) PNBs status (biopsy naïve vs. PNBs); (2) number of PNBs (0 vs. 1 vs. ≥ 2); (3) histology at last PNB (no vs. negative vs. HGPIN/ASAP). Kaplan-Meier plots and multivariable Cox models tested any-cause and ISUP GG upgrading discontinuation rates. RESULTS: Overall, 760 (79.1%) vs. 201 (20.9%) patients were biopsy naïve vs. PNBs. Specifically, 760 (79.1%) vs. 138 (14.4%) vs. 63 (6.5%) patients had 0 vs. 1 vs. ≥ 2 PNBs. Last, 760 (79.1%) vs. 134 (13.9%) vs. 67 (7%) patients had no vs. negative PNB vs. HGPIN/ASAP. PNBs were not associated with any-cause discontinuation rates. Conversely, PNBs were associated with lower rates of ISUP GG upgrading: (1) PNBs vs. biopsy naïve (HR:0.6, p = 0.04); (2) 1 vs. 0 PNBs (HR:0.6, p = 0.1) and 2 vs. 0 PNBs, (HR:0.5, p = 0.1); (3) negative PNB vs. biopsy naïve (HR:0.7, p = 0.3) and HGPIN/ASAP vs. biopsy naïve (HR:0.4, p = 0.04). However, last PNB ≤ 18 months (HR:0.4, p = 0.02), but not last PNB > 18 months (HR:0.8, p = 0.5) were associated with lower rates of ISUP GG upgrading. CONCLUSION: PNBs status is associated with lower rates of ISUP GG upgrading during AS for PCa. The number of PNBs and time from last PNB to PCa diagnosis (≤ 18 months) appear also to be critical for patient selection.
Keywords: prostatická intraepiteliální neoplazie; Biopsy naïve; biopsie; Upgrading; pozorné vyčkávání; lidé; Any-cause discontinuation; Previous negative biopsies; nádory prostaty; Prostatic Neoplasms; Humans; retrospektivní studie; Male; Biopsy; Prostatic Intraepithelial Neoplasia; mužské pohlaví; Active surveillance; Retrospective Studies; Watchful Waiting